RASIO KEUANGAN YANG MEMPENGARUHI KONDISI FINANCIAL DISTRESS PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ahnan Kasogi; Yuliah Yuliah; Ahmad Mukhlis (Universitas Bina Bangsa, 2022)
This study aims to determine the effect of Debt to Asset Ratio (DAR), Current Ratio (CR), Total Assets Turn Over (TATO), and Return On Equity (ROE) on financial distress conditions, either partially or simultaneously. This study uses a quantitative approach with secondary data. Purposive sampling was used to choose the sample for this study, so that 48 companies were obtained from a population of 90 manufacturing enterprises in the basic and chemical industrial sectors listed on the Indonesia Stock Exchange from 2017 to 2021. The analytical technique were using logistic regression with the SPSS version 26 program. The results obtained shows that the Debt to Asset Ratio (DAR) partially has a positive effect on financial distress, while Current Ratio (CR), Total Assets Turn Over (TATO), and Return On Equity (ROE) partially have a negative effect on financial distress. According to simultaneous testing, financial distress circumstances are affected by the Debt to Asset Ratio (DAR), Current Ratio (CR), Total Assets Turn Over (TATO), and Return On Equity (ROE).